Nanocrystalline N-Doped TiO2 Powders: Mild Hydrothermal Synthesis and Photocatalytic Degradation of Phenol under Visible Light Irradiation - Junna Xu; Feng Wang; Wenxiu Liu; Wenbin Cao (International Journal of Photoenergy)
Nitrogen-doped TiO2 powders have been prepared using technical guanidine hydrochloride, titanyl sulfate, and urea as precursors via a mild hydrothermal method under initial pressure of 3MPa, 150∘C holding for 2h without any postheat treatment for crystallization. The nanocrystalline N-doped TiO2 powders were composed of anatase TiO2 by XRD. The grain size was estimated as about 10 nm, and the BET specific surface area of the powder was measured as 154.7 m2/g. The UV-visible absorption spectra indicated that the absorption edge of the N-doped TiO2 powders had been red shifted into the visible light region. The photocatalytic performance of the synthesized powders was evaluated by degradation of phenol under visible light irradiation. And the effects of the catalyst load and the initial pH value on the photodegradation were also investigated.